Two regional power system PSO PID Control Research - Jingfang Wang (Institute of Advanced Engineering and Science, 2015)
In this paper, we propose a PID parameter tuning of particle swarm optimization for multi-objective optimization characteristics of two regional power system PID controller design. By defining a comprehensive consideration of system output overshoot, rise time and the fitness function term steady-state error indicators, such as the ITAE, and in accordance with the performance requirements of the actual control system, appropriate weighting of each index item. Use with base and improved particle swarm algorithm for multi-objective optimization PID. PSO optimization algorithm has good global search ability and high convergence rate. You can respond to the PID controller tuning parameters directly from the output of the PID control system easily balance between speed and stability control systems. After using PSO-PID control in two regional power system ，the amount of overshoot in the step total response downs from 65% to 5%. Adjust time downs from 12 seconds to 3 seconds. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6835